Hyaluronic Acid-Modified Nanoplatforms as a Vector for Targeted Delivery of Autophagy-Related Gene to the Endometriotic Lesions in Mice - Zhao, Mengdan; Zhang, Meng; Yu, Qin; Fei, Weidong; Li, Tiantian; Zhu, Libo; Yao, Yao; Zheng, Caihong; Zhang, Xinmei (Frontiers in Bioengineering and Biotechnology, 2022)
This investigation probed endometriosis treatment using targeted nanoparticles (NPs) to modulate autophagic activity. To that end, a novel form of polymer-based NP gene delivery platform consisting of polyethyleneimine (PEI)-conjugated to stearic acid (SA) and nucleotides (DNA/siRNAs) and enclosed by hyaluronic acid (HA) was prepared. CD44 is highly upregulated in cystic lesions, and HA-CD44 binding this specific nanoplatform was used to achieve targeted drug delivery to CD44-expression endometriotic tissues. The expression of autophagy-related genes was modulated to explore the importance of this process in the development of endometriosis. By inducing autophagic activity, we were able to reduce the size of endometriotic cysts and suppress the development of ectopic endometrial. To further confirm the relationship between autophagic activity and this disease in humans and animals, numbers of autophagic vesicles and autophagic protein expression were assessed in lesion tissue samples from patients, revealing good consistency between animal and human data. Overall, these data revealed the ability of this (PEI-SA/DNA) HA gene delivery system to regulate autophagic activity and to thereby aid in the treatment of endometriosis.